Analisis Kinerja Keuangan Perusahaan dengan Metode Economic Value Added (EVA) (Studi Kasus Perusahaan Otomotif Go Publik) - Mubarok, Rahman; Dewi, Farida Ratna (Jurnal Manajemen dan Organisasi, 2010)
Global economics crisis causes the fall of world stock. This is causes weakens it share in BEI, including sector otomotif.  BEI has some stock indexes as movement indicator of stock price, one of them is index Kompas 100.  This Index represents of  about 70-80 percent market capitalization value total of share  in BEI.  However, that can be different with other index, so that be necessary to measure of each corporate performance with using Economic Value Added (EVA) method.    EVA is used to measure of corporate performance based of the value.  value added will be create, if the retained earning more than cost of capital.  From two company analized during the 2007 to 2008 period,  there is only one of corporate have a performance increase at 2008, that is PT Multistrada Arah Sarana Tbk, this is mean the corporate has been investor expectation filled.  Differ from PT Multistrada, PT Gajah Tunggal at 2008 have a performance decrease. At 2007 it have positive value of EVA, but at 2008 value of EVA get down to negative. This is happen cause of dead loss in consequence of global economics crisis. For the companies that give the negative value, it  better find out more strategies so it  can make their profit rise and also to push the capital cost with choosing the lowest capital structure. Beside that, the companies also should erase the activities that can caused the value of the company becoming less.